157 The epidemiology of congenital myasthenic syndromes in Northern Ireland. Issue 3 (9th February 2012) - Carr, A; Cardwell, C; O'Reilly, D; McCarron, P O; McConville, J
Abstract : Background: Congenital myasthenic syndromes (CMS) are a heterogeneous group of disorders due to inherited abnormalities in neuromuscular transmission. To date, information on the frequency of these conditions comes from specialist centre case series reports. Population-based data are lacking. Methods: Cases were ascertained from systematic review of patients attending the regional neuromuscular clinic over the past 30 years and from those identified and excluded from an epidemiological study of autoimmune myasthenia gravis in the area. Cases were confirmed clinically, genetically and with neurophysiological examination. Results: 16 cases of CMS were identified in the region giving a prevalence rate of 8.2 per million (95% CI 6.0 to 10.4) and an estimated incidence of 0.2 (95% CI 0.06 to 0.62) per million person-years. Age of onset: 0–60 years (mean: 15.2 years); four females, 12 males. Dok-7 syndromes were the most common (43.9%) followed by slow channel (21.4%) and acetylcholine receptor deficiency syndromes (14.3%). One case was fatal and diagnosed at post-mortem: mortality rate 0.1 (95% CI 0.01 to 0.71) per million person years. All cases responded well to specific treatments with functional improvement. Conclusion: This data highlights characteristics useful for recognition of CMS within the general neuromuscular clinic. Their treatability makes recognition and genetic diagnosis vital. This is the first population-based description of these conditions.